The reasons of treatment delay of breast cancer patients with regard to psychological factors. Study results - Brandys, Anna; Rysz, Barbara; Żuchowska-Vogelgesang, Beata; Rachtan, Jadwiga; Pawlicki, Marek (Contemporary Oncology/Współczesna Onkologia, 1999)
Results of own studies on reasons for treatment delay of breast cancer patients are presented. In group of 117 patients median delay of 7.5 mounths is reported in 30.5%. Patient related delay is caused mainly by use of alternative medicine and psychological factors. Prolonged and not adequate diagnostic procedure and treatment are responsible for delay at every 3-rd patient. Despite postgraduated training described situation has been ameliorated only insignificantly in last 20 years.